Effect of Work Environment and Compensation on Employee Performance with Job Satisfaction as a Mediation Variable - Gabriel Indripriarko; M. Havidz Aima (Publikasi Indonesia, 2022)
This study aims to examine and analyze whether the work environment has an influence on job satisfaction, compensation has an influence on job satisfaction, the work environment has an influence on employee performance, compensation has an influence on employee performance, job satisfaction has an influence on employee performance, work environment and compensation simultaneously has an influence on employee performance, work environment, compensation, and job satisfaction simultaneously has an influence on employee performance, job satisfaction has an influence on mediating the work environment on employee performance, and job satisfaction has an influence on mediating compensation on employee performance. The population of this study was employees of an electronic component manufacturing company in Cikarang, with a total sample of 222 people. The data analysis method used SEM-PLS. The results of this study are the work environment has a significant positive effect on job satisfaction, compensation has a positive and significant effect on job satisfaction, the work environment has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance. Employee Performance, Work Environment, and Compensation have a positive effect on Job Satisfaction, Work Environment, Compensation, and Job Satisfaction simultaneously have a significant positive effect on Employee Performance, Job Satisfaction mediates Work Environment on Employee Performance, Job Satisfaction mediates Compensation on Employee Performance